Irreversible magnetostriction and magnetization of the superconduting 2H-NbSe₂ single crystals in a peak-effect regime - Eremenko, V.V.; Sirenko, V.A.; Shabakayeva, Yu.A.; Gammel, P.L. (Физика низких температур, 2002)
Magnetostriction mea sure ments in the mixed state of superconducting 2H-NbSe₂ single crystals under in-plane magnetic fields 0-12 T have revealed a peak on the magnetostriction versus magnetic field dependences in the vicinity of the upper critical field Hc₂. The peak value of the longitudinal magnetostriction is higher by more than an order of magnitude in comparison with that of the trans verse magnetostriction when measured along the hexagonal axis. Analysis of the measured field dependences of the magnetostriction and magnetization of 2H-NbSe₂ allows one to relate the observed peculiarities of magnetostriction with the loss of order in the lat tice of Abrikosov vortices, which occurs by a first-order phase transition. Remove selected